93.2k views
0 votes
If(1) = 37
(f(n) = f(n-1). 0.3
Find an explicit formula for f(n).​

User Ribs
by
5.6k points

2 Answers

5 votes

Answer:

f(n) = 37 (0.3)ⁿ⁻¹

Explanation:

I did it on khan and i got it right

User Terris
by
4.8k points
6 votes

Answer:

f(n) = 37 (0.3)ⁿ⁻¹

Explanation:

Given;

f(1) = 37

f(n) = f(n-1). 0.3

find an explicit formula for f(n),

To determine the explicit formula for the given sequence, we consider the first term given (37) and possible way to obtain this value at a given common difference of 0.3.

The first term can be gotten if we simplify the sequence as shown below.


explicit \ formula \ for \ f(n) = 37(0.3)^(n-1)

where;

37 is the first term

n is a natural number

0.3 is the common difference

Therefore, the explicit formula for f(n) = 37 (0.3)ⁿ⁻¹

User David Culbreth
by
5.6k points